# Solve for k k-1=(k+3)/2 k-1=k+32
Move all terms containing k to the left side of the equation.
Subtract k+32 from both sides of the equation.
k-1-k+32=0
To write k as a fraction with a common denominator, multiply by 22.
k⋅22-k+32-1=0
Combine k and 22.
k⋅22-k+32-1=0
Combine the numerators over the common denominator.
k⋅2-(k+3)2-1=0
Simplify the numerator.
Move 2 to the left of k.
2⋅k-(k+3)2-1=0
Apply the distributive property.
2k-k-1⋅32-1=0
Multiply -1 by 3.
2k-k-32-1=0
Subtract k from 2k.
k-32-1=0
k-32-1=0
To write -1 as a fraction with a common denominator, multiply by 22.
k-32-1⋅22=0
Combine -1 and 22.
k-32+-1⋅22=0
Combine the numerators over the common denominator.
k-3-1⋅22=0
Simplify the numerator.
Multiply -1 by 2.
k-3-22=0
Subtract 2 from -3.
k-52=0
k-52=0
k-52=0
Multiply both sides of the equation by 2.
2⋅k-52=2⋅0
Simplify both sides of the equation.
Cancel the common factor of 2.
Cancel the common factor.
2⋅k-52=2⋅0
Rewrite the expression.
k-5=2⋅0
k-5=2⋅0
Multiply 2 by 0.
k-5=0
k-5=0
Add 5 to both sides of the equation.
k=5
Solve for k k-1=(k+3)/2

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top